Safety climate, nursing organizational culture and the intention to report medication errors: A cross-sectional study of hospital nurses. - Hyun Young Lee; Eun-Kyung Lee (Nursing Practice Today, 2021)
Background & Aim: Medication errors are the second most common accident after the fall accident in hospitals. Medication errors are a threat to patient safety. It is important to find the cause of such errors so that we can reduce them. However, the rate of medication error reporting is low. This study aimed to explore the factors associated with the intention to report medication errors among general hospital nurses. Methods & Materials: A cross-sectional study design was used. The participants were 171 registered nurses working in 4 general hospitals in South Korea. Convenient random sampling was used to select participants. Data were collected using mobile self-report structured questionnaires that covered general characteristics, medication errors and the intention to report them, the safety climate, and the nursing organizational culture. The data collection period was from March 14 to April 6, 2018. The data were analyzed by descriptive statistics, the Pearson correlation coefficients, and multiple regression analysis. Results: The mean scores of the intention to report medication errors and safety climate were 5.20±1.40 and 3.04±0.47, respectively. Each mean score of nursing organizational culture types was hierarch-oriented culture 3.63±0.51, relation-oriented culture 3.13±0.69, task-oriented-culture2.99±0.56, and innovation-oriented culture 2.85±0.67. Significant factors associated with the intention to report medication errors were the safety climate (ß=.26, p=.001), a task-oriented culture (ß=.16, p=.023), educational level (ß=-.19, p=.006), the experience of medication errors (ß=.19, p=.006), and male (ß=-.18, p=.011). Conclusion: This study found that the safety climate of the hospital, task-oriented culture of the nursing organization, education level, experience of medication errors, and gender associated with the intention to report medication errors. It is necessary to find ways to improve the safety climate of the hospital and the task-oriented culture of the nursing organization and establish a strategy for improving the intention to report medication errors for male nurses and nurses with medication errors.